2011
DOI: 10.1002/pro.2002
|View full text |Cite
|
Sign up to set email alerts
|

Protein topology from predicted residue contacts

Abstract: Residue contacts predicted from correlated positions in a multiple sequence alignment are often sparse and uncertain. To some extent, these limitations in the data can be overcome by grouping the contacts by secondary structure elements and enumerating the possible packing arrangements of these elements in a combinatorial manner. Strong interactions appear frequently but inconsistent interactions are down-weighted and missing interactions up-weighted. The resulting improved consistency in the predicted interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 60 publications
0
36
0
Order By: Relevance
“…The extraordinary improvements in DNA sequencing technology, aided by advanced statistical analysis, have now provided the keys to unlock this evolutionary information. Several groups have demonstrated that extracting covariation information from sequences is sufficient not only to estimate which pairs of residues are close in three-dimensional space 1521 but also to fold a protein to reasonable accuracy 15,2225 (Table 1). In addition to being predictive of contacts in a protein, these pairs of covarying residues should also be predictive of functional sites (Fig.…”
Section: Covariation and The Problem Of Transitive Correlationsmentioning
confidence: 99%
“…The extraordinary improvements in DNA sequencing technology, aided by advanced statistical analysis, have now provided the keys to unlock this evolutionary information. Several groups have demonstrated that extracting covariation information from sequences is sufficient not only to estimate which pairs of residues are close in three-dimensional space 1521 but also to fold a protein to reasonable accuracy 15,2225 (Table 1). In addition to being predictive of contacts in a protein, these pairs of covarying residues should also be predictive of functional sites (Fig.…”
Section: Covariation and The Problem Of Transitive Correlationsmentioning
confidence: 99%
“…Integrating the DCA-predicted contacts into coarse-grained physical models of proteins such as structure-based models (SBMs) (15)(16)(17)(18)(19) led to predictions on protein-protein interactions (20)(21)(22) as well as tools to aid the prediction of native structures (19,(23)(24)(25). The idea of using predicted contacts to estimate native structures was also explored by other methodologies (26,27). Here, we show that DCA predicts important structural interactions related not only to the native state but also to distinct functional conformational states of a protein, including intermediates.…”
mentioning
confidence: 99%
“…Among the most popular are Pearson correlation, maximum likelihood approaches, Bayesian statistics, chi-square-like methods and statistical coupling analysis [10]. In particular, approaches from information theory that use mutual information and Shannon entropy have recently been applied to three-dimensional structure prediction with promising results [1-8]. …”
Section: Box 1 Identification and Interpretation Of Co-evolving Posimentioning
confidence: 99%
“…In this approach, the accuracy of the strongest direct interactions can significantly be improved by sparse inverse covariance estimation, in which the inverse covariance matrix is numerically estimated while iteratively removing weaker interactions. An efficient algorithm known as graphical LASSO has been used to transfer this principle to co-evolutionary correlation problems in order to predict residue contacts [1,4]. …”
Section: Box 1 Identification and Interpretation Of Co-evolving Posimentioning
confidence: 99%
See 1 more Smart Citation